Behavioral fluency and mathematics intervention research: A review of the last 20 years. (20th November 2018) - Stocker, James D.; Schwartz, Rachel; Kubina, Richard M.; Kostewicz, Douglas; Kozloff, Martin
Abstract : Behavioral fluency refers to the relationship between the achievement of performance standards, or frequency ranges of behavior, and critical learning outcomes. Over the past 20 years, Precision Teaching and related research have contributed a number of studies examining behavioral fluency. The subsequent review investigates the empirical evidence from mathematics intervention research. Several studies suggest numerical markers that best support behavioral fluency. Results indicate that fluency interventions set to performance standards increased behavioral fluency and associated critical learning outcomes; however, more research is warranted to operationalize and standardize each outcome to the principles of behavior and numerical markers that constitute behavioral fluency.